2017
DOI: 10.1002/pon.4570
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence and associated risk factors of suicide mortality among breast cancer patients

Abstract: There have been no identifiable improvements in preventing suicide mortality in the United States. Younger age, male sex, race, marital status, and undergoing surgery are independent risk factors for committing suicide, especially in the first year after diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 36 publications
(59 reference statements)
4
49
2
Order By: Relevance
“…Our study showed that the suicide rates of the white race and other races were respectively 2.77 and 1.34 times higher than that of the black race. Furthermore, the black race was proved to be a protective factor of suicide, matching the findings in previous investigations . In terms of the black race, this finding might be explained by religious beliefs, family support, and culture of rejecting suicide .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Our study showed that the suicide rates of the white race and other races were respectively 2.77 and 1.34 times higher than that of the black race. Furthermore, the black race was proved to be a protective factor of suicide, matching the findings in previous investigations . In terms of the black race, this finding might be explained by religious beliefs, family support, and culture of rejecting suicide .…”
Section: Discussionsupporting
confidence: 86%
“…Some recent publications showed that older age was a predictor of suicide for cancer patients and the common population . Interestingly, older breast cancer patients who fare better in terms of functional status than younger patients were less likely to commit suicide . In our study, a tendency of increased suicide rate with age was also observed, although without statistical association.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…This is one of the most representative large tumor databases in North America, which covers approximately 28% of the US population 29,30 . SEER has collected information on the incidence, prevalence, mortality, and other evidence‐based medicines of cancer patients in some US states and counties for decades, providing valuable information on cancer diseases for the majority of clinical medical staff 31 . Especially, it provides a broad path for the study of malignant tumors and rare tumors.…”
Section: Medical Public Database Overviewmentioning
confidence: 99%